Coronavirus-19: Possible Therapeutic Implications of Spironolactone and Dry Extract of Glycyrrhiza glabra L. (Licorice) - Armanini, Decio; Fiore, Cristina; Bielenberg, Jens; Sabbadin, Chiara; Bordin, Luciana (Frontiers in Pharmacology, 2020)
https://clinicaltrials.gov/ (NCT044241349, NCT043465887, NCT04487964)